NEW CHAPTER OF DIPLOMATIC RELATION BETWEEN INDONESIA-AMERICA UNDER NEW CONTRACT OF FREEPORT-MCMORAN - Shobaruddin, Muhammad (Natapraja, 2018)
Freeport-McMoran has explored valuable natural resources in Indonesia by digging gold and copper in Papua since 1967. This essay analyzed the impacts of this new agreement toward the future of the US-Indonesia bilateral relationship as well as reveal Jokowi’s diplomatic approach to gain this agreement. The analysis in this article uses a qualitative approach based on secondary data. The data collected from the official reports of Freport-Mcmoran and other relevant sources. Indonesian government always try to lobby US government through soft diplomacy in order to maintain bilateral relationship. The renegotiation allows the contract extension of the company (until 2041) which will be expired in 2021. Indonesian government still need the US as bilateral partner since this super power country has already played significant roles by contributing economic growth, democratic development, and national security in Indonesia. Hence, Indonesia is carefully approaching the US government to avoid negative effects of Indonesia-Freeport’s renegotiation.